2015
DOI: 10.1088/0268-1242/30/11/114012
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and strain properties of core-shell GaAs/AlGaAs nanowires

Abstract: GaAs/AlGaAs core-shell nanowires were grown on Si(111) by Ga-assisted molecular beam epitaxy via the vapor-liquid-solid mechanism. High-resolution and scanning transmission electron microscopy observations showed that nanowires were predominantly zinc-blende single crystals of hexagonal shape, grown along the [111] direction. GaAs core nanowires emerged from the Si surface and subsequently, the nanowire growth front advanced by a continuous sequence of (111) rotational twins, while the AlGaAs shell lattice was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Typical FE-SEM images of core-shell GaAs/InGaAs NWs are shown in Fig. 2 , where we observe that over 60 % of the NWs are grown along the [111] direction perpendicular to the substrate, while the rest grow along inclined {111} crystallographic orientations, consistent with results reported previously for similar growth conditions [ 15 , 16 ]. By closer inspection of the SEM images, most of the core-shell NWs display characteristic hexagonal morphology with {110} lateral facets (cf .…”
Section: Resultssupporting
confidence: 87%
“…Typical FE-SEM images of core-shell GaAs/InGaAs NWs are shown in Fig. 2 , where we observe that over 60 % of the NWs are grown along the [111] direction perpendicular to the substrate, while the rest grow along inclined {111} crystallographic orientations, consistent with results reported previously for similar growth conditions [ 15 , 16 ]. By closer inspection of the SEM images, most of the core-shell NWs display characteristic hexagonal morphology with {110} lateral facets (cf .…”
Section: Resultssupporting
confidence: 87%
“…Another interesting finding is that relaxation at the outer shell sidewalls increases ( ϵ ρφ decreases) with increasing shell radius. This is in line with MD simulations, as relaxation spreads from the vertices toward the perimeter of thicker shell NWs . Moreover, the ϵ ρφ variation along the circumradius R (<112> directions) of the core‐shell hexagons as a function of the shell's Al% content, for S/NW ratio 0.5, is given in Figure (c).…”
Section: Resultssupporting
confidence: 84%
“…In our case, GaAs/Al x Ga (1− x ) As core‐shell NWs were grown on Si(111) by MBE. Cross‐sectional TEM micrographs showed that NWs consist of two usually concentric hexagons, over 1 μm long along the <111> growth direction and 80–100 nm thick, bounded by {110} crystal facets [Figure (a) and (b)] . Based on these observations we constructed the 3‐D shape model to be used in FE calculations, as shown in Figure (c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations